Schweinfurthins: Lipid Modulators with Promising Anticancer Activity. Issue 8 (17th October 2018) - Koubek, Emily J.; Weissenrieder, Jillian S.; Neighbors, Jeffrey D.; Hohl, Raymond J.
Abstract: The schweinfurthin family of compounds displays exciting potent and differential cytotoxicity against human cancer cell lines. Currently, the effect of schweinfurthins on tumor development and progression is being explored in animal models of cancer with promising results. The first schweinfurthin family member, vedelianin, was isolated in 1992, followed by other schweinfurthins in 1998. This opened up the door for the synthesis of additional analogs. At present, the focus of research lies on delineating the mechanism of schweinfurthin action and identifying the nature of sensitivity. It appears that many of the intracellular effects of schweinfurthins are due to, or impacted by, the effect of schweinfurthins on lipid metabolism, synthesis, and homeostasis. These effects include impaired trafficking from the trans‐golgi network, disruption of lipid rafts, changes in oxysterol‐binding protein activity, and interference with the isoprenoid biosynthesis pathway (IBP). Cancer cells are known to rely heavily on fatty acid, lipid, and sterol synthesis for growth and proliferation. Therefore, compounds that target these needs, such as schweinfurthins, display promise as novel therapeutics. This timely review will take an in‐depth look at the history of schweinfurthins, their synthesis, where the research presently stands, and the questions that remain.